"Not just dogs, but rabid dogs": tensions and conflicts amongst research volunteers in Malawi. Issue 1 (1st January 2018) - Phiri, Mackwellings; Gooding, Kate; Nyirenda, Deborah; Sambakunsi, Rodrick; Kumwenda, Moses Kelly; Desmond, Nicola
ABSTRACT: Building trust between researchers and communities involved in research is one goal of community engagement. This paper examines the implications of community engagement for trust within communities, including trust among community volunteers who assist with research and between these volunteers and other community members. We describe the experiences of two groups of community volunteers recruited as part of an HIV and TB intervention trial in Malawi: cluster representatives, recruited both to act as key informants for TB suspects and mortality reporting and to identify and report community concerns, and community counsellors, recruited to provide semi-supervised HIV self-testing. We examine tensions experienced due to playing multiple roles, and the implications of volunteer responsibilities for short- and long-term community relationships. Data was collected through a workshop, in-depth interviews and focus group discussions with volunteers and community members. While the volunteer system initially enhanced trust among volunteers and with the community, relationships deteriorated when cluster representatives assumed an additional supervisory role part-way through the trial. Combined with challenging recruitment targets and unequal power relations between volunteers, this new role damaged trust, with implications for volunteer well-being and social relationships. These experiences suggest researchers should consider potential social implications when designing community engagement systems.